(3OjhGf GHf Ndha GdCfOdSjs - (3RqQhb , TgGH GdOjf CHh GdYHGS CMeO Hf eMeO Hf YHO GdQMef GdaGSj, CHh GdYHGS,J (B899 (3g` s ((3YHOGdSdGe Hf Ydj HWYeI GdHbGYj s)
(3ChdgG (B:s
(3EP hGHd Ce bGeI gjaGA hefGUd Ce ebdI hWaGA s
(3BNQgG (B:s
(3hbO QBfj LQMJ hLfJg aGbJkqU ef egLJj HfXQJg s
(3GdOjhGf eQJH Ydi GdMQhas
(3bQf GdfSN (B:s
(3GdbQf GdKGfj YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B1 - (3U (B91 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B2 - (3U (B118s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B1 - (3bSe (B3 - (3U (B100 s
Keywords: (3GdCOHs